A fuzzy logic based magnetic ball bearing system - Abdullah, Shahrum Shah (Penerbit UTM, 2008)
Fuzzy Logic Control are useful when the processes are too complex for analysis by conventional quantitative techniques or when the available sources of information are interpreted qualitatively, inexactly, or uncertainly (Lee, 1990). It does not require any system modeling or complex mathematical equations governing the relationship between inputs and outputs (Aptronix, 1999). Fuzzy rules are very easy to learn and use, even by nonexperts. It typically takes only a few rules to describe systems that may require several lines of conventional software code, which reduces the design complexity (Aptronix, 1999). This paper illustrates a simple way of controlling a non-linear, 3rd order and unstable system using Fuzzy logic. The design procedure utilizes MATLAB ® Fuzzy Logic toolbox and was implemented using SIMULINK ® version 7.1.